2020
DOI: 10.1186/s40834-020-00116-7
|View full text |Cite
|
Sign up to set email alerts
|

Family planning practices of women working in the Cambodian garment industry: a qualitative study

Abstract: Background: Women working in Cambodian garment factories have unmet needs for family planning (contraception and safe abortion) services, because of their background and living conditions. This study describes their experiences regarding abortion and contraception as part of a larger project to develop an intervention to support comprehensive post-abortion care. Methods: We conducted semi-structured interviews with women seeking abortion services at private health facilities. In addition, we interviewed the pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“… 8 , 12 , 26 , 30 , 31 , 32 , 33 , 35 , 37 , 39 , 40 , 41 , 42 The woman may then disclose or conceal the pregnancy or her initial decision to her close networks including partner, parents, siblings, teachers and other close friends depending upon the level of trust, perceived reaction to the woman's decision and expected support. 8 , 12 , 31 , 33 , 35 , 36 , 38 , 39 , 43 , 44 , 45 , 48 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 , 12 , 26 , 30 , 31 , 32 , 33 , 35 , 37 , 39 , 40 , 41 , 42 The woman may then disclose or conceal the pregnancy or her initial decision to her close networks including partner, parents, siblings, teachers and other close friends depending upon the level of trust, perceived reaction to the woman's decision and expected support. 8 , 12 , 31 , 33 , 35 , 36 , 38 , 39 , 43 , 44 , 45 , 48 …”
Section: Resultsmentioning
confidence: 99%
“…The final abortion decision may be made solely or primarily by the woman herself, jointly with her partner or others, or by others without or with minimal involvement of the woman. 7 , 8 , 10 , 12 , 26 , 27 , 29 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 74 However, even cases in which the majority of the decisions are made by woman, male partners and/or parents still influenced her decision. 7 , 35 , 39 , 44 , 74 Thus, decisions made by woman may either be passive in which the woman simply agrees to the decision imposed onto her by others 8 , 30 , 32 , 35 , 37 , 38 , 39 , 44 , 48 ,…”
Section: Resultsmentioning
confidence: 99%
“…10 A qualitative study conducted in Phnom Penh city, Cambodia, confirmed that if one reduces fertility, there will be fewer children and it would be easier to earn a living. 11 Another positive attitude was seen in subjects who mentioned that they would like to use contraception after delivery. This would motivate women to practice family planning using contraceptive methods.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from these interviews are reported elsewhere. 12 During the course of the project, we organised several meetings to share and discuss behaviours observed in research that could feasibly be targeted and potential interventions resulting from the needs assessment activities, and then design, produce and refine a pilot intervention. In order to address limitations in the provision of accessible contraceptive information and information materials for factory workers in general and specifically at the time of seeking medical abortion, we decided to make three 'edutainment' videos about family planning and one instructional video about how to take medical abortion correctly.…”
Section: Open Accessmentioning
confidence: 99%
“…15 The videos were designed to target barriers to contraception use that were identified in the needs assessment, ethnographic and interviews studies. 12 The videos were released through MSIC's communication channels and their impact was evaluated by an independent digital media company (Havas Champagne media). 16 Patient and public involvement Neither patients nor the public were involved in the development of the research question, study design or outcome measures.…”
Section: Open Accessmentioning
confidence: 99%